Inhibition effect of Rosella (Hibiscus sabdariffa L.) petal extract in Hard-Candy against Streptococcus mutans - Maria Erna Kustyawati; Samsu udayana Nurdin; Dyah Putri Larassati; Anna Pintalita (Hasanuddin University Food Science and Technology Study Program, 2022)
Hard candy with the addition of roselle flower petal extract is considered an innovative product to improve the functional properties and sensory acceptance of roselle hard candy. The aim of the research was to determine the best concentration of rosella petal extract in hard candy that provided maximal bacterial effect against Streptococcus mutans and acceptable sensory. The research was arranged in Randomized Complete Block Design (RCBD) with six treatments and three replications. The treatments were the ratio concentration of rosella petal extract: water in the formulation for hard candy making (P). The Anova was performed and followed by LSD test at 5%. The results showed that different concentrations of rosella petal extract and water had a significant effect on total microbes, inhibition of S. mutans, and sensory analysis of rosella petal extract hard candy. The best treatment was the formulation of P4 (rosella petal extract: water, 15: 85 mL). It produced rosella petal extract hard candy with a total microbial of 1.5 x 102 cfu/g and S.mutans inhibition of 8.43 mm, and met the SNI 3547.1:2008 requirement standards, except for the reducing sugar content. It was concluded that the hard candy with the additional ingredient of rosella petal extract could potentially help prevent the formation of dental plaque.